Kembangkan Potensi Situs Watu Lumpang sebagai Wisata Sejarah Desa Kembangkuning, Kabupaten Boyolali - Yuniar Prawesti; Eudia Christina Wulandari; Tri Yulianingsih; Dwi Yogo Utomo; Melani Pratika Yudaningrum (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Kembangkuning Village has potential as a historical attraction. The potential of historical attraction is the Watu Lumpang Site that rarely visited even by the local community. Therefore, the idea to optimize the potential of Kembangkuning Village to become a historical tourism village that will be known by the wider community. The method used in this service activity is descriptive qualitative method with data collection in the field through observation, identification, interviews, and documentation. The result of this community service activity to change the mindset of local people to consider the Watu Lumpang Site as a dangerous place are slowly starting to disappear. This is proven by the event of area cleanup activities with local residents after this activity was carried out.